Efisiensi Beberapa Macam Alat Dewatering Untuk Pengelolaan Lumpur Industri Elektroplating - Sri Pudji Rahayu; Dwinna Rahmi; Ukar Tarwiyono (Balai Besar Kimia dan Kemasan, 1998)
Many methods for dewatering of sludge, such as natural evaporate by sun or by means of equipment. Three kind methods of electroplating sludge dewatering by using equipment hare been studied, i.e : centrifugal, filter press and vacuum filter. The result shows that centrifugal has the best performance in term of reduction speed of sludge weight, moisture content of dry cake, and also time. The use of coagulant, thickener and polymerin dewatering can increase flock formation , therefore can accelerate the process. Coagulant addition is necessary in dewatering by using centrifugal method.